2017
DOI: 10.3390/en10111739
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Aircraft Power Systems Based on a Unified Large Signal Model

Abstract: Abstract:Complex power electronic conversion devices, most of which have high transmission performance, are important power conversion units in modern aircraft power systems. However, these devices can also affect the stability of the aircraft power system more and more prominent due to their dynamic and nonlinear characteristics. To analyze the stability of aircraft power systems in a simple, accurate and comprehensive way, this paper develops a unified large signal model of aircraft power systems. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Having considered multiple CPLs, authors in [105] analyzed the stability of a hybrid ac-dc MEA EPS. Also, large signal and small signal stability based on Lyapunov methods and robust stability methods were studied in [106] and [107], respectively. To combat and eliminate the problem caused by CPLs, authors in [108] found the solution in real-time power estimation employed and developed by an adaptive back stepping controller.…”
Section: B Stabilitymentioning
confidence: 99%
“…Having considered multiple CPLs, authors in [105] analyzed the stability of a hybrid ac-dc MEA EPS. Also, large signal and small signal stability based on Lyapunov methods and robust stability methods were studied in [106] and [107], respectively. To combat and eliminate the problem caused by CPLs, authors in [108] found the solution in real-time power estimation employed and developed by an adaptive back stepping controller.…”
Section: B Stabilitymentioning
confidence: 99%
“…At first, the model for the power electronics-dominated power system analyzed must be determined under an appropriate approach [27]. e high penetration of different types of power electronics in one grid brings out various nonlinear properties such as controller delays and switching harmonics.…”
Section: Transient Stability Analysis Process Based On Direct Methodsmentioning
confidence: 99%
“…In [59], the small‐signal stability criterion for the equilibrium point of the cascaded system with a current‐mode controlled source converter and a CPL is derived using the Lyapunov linearisation method. A similar study for aircraft power system is carried out in [60]. In this case, the Lyapunov method is simple to implement and has predictive characteristics [59].…”
Section: Lyapunov Linearisation Methodsmentioning
confidence: 99%